Social Political Differentiation of Electoral Moods of the Population of the Ukrainian SSR after World War II - Stasiuk, Oleksandra (Faces of War, 2024)
In this paper, the main manifestations of the electoral moods of the population of the Ukrainian SSR during the elections to the Supreme Soviets of the USSR, the Ukrainian SSR and local authorities in 1946–1947 are considered. The generally low level of interest of the population in political actions, such as election campaigns, is emphasised due to the difficult social political and economic situation in the state. The factors that determine the electoral behaviour of voters and the causes of social deviations are analysed. The paper presents the stratification of citizens’ electoral moods according to socio-political indicators and in the regional dimension, describing in detail the attitude to the elections of such social groups as workers, peasants, petty bourgeois, intelligentsia, women, etc. It is noted that the geography of critical statements proves the similarity of the electoral moods of the population in different regions of the Republic. However, the motivation for the protests and their public manifestation by the residents of ‘Great Ukraine’ (i.e., eastern and central Ukraine, which was under the rule of the Russian Empire and the USSR) and the western region are radically different. If, in most of the territory of the Ukrainian SSR, citizens accepted the demands of the authorities and were included in the electoral process, Western Ukrainians massively boycotted them. The boycott of the elections by the Western Ukrainian population was caused by a protest against the repeated forced Sovietisation of the region, the predatory economic policy of the authorities, as well as repressions against participants in the national liberation movement. Equally, Western Ukrainians protested primarily for ideological reasons, not accepting the values of the Soviet power and considering it an occupational force, while for the inhabitants of Great Ukraine, the everyday, material aspect turned out to be the most critical issue.